Responding to literature 3-6 : activities that build confident readers and writers - Hetzel, June.; Campbell, Jenny (Huntington Beach, CA : Creative Teaching Press, 2002)
Contains mini-lessons, activities, reproducibles, and graphic organizers designed to help students in grades three and six improve their writing skills.
"3-6.
"CTP 3368 3-6"--Cover.
Professional.
Professional
Keywords: Creative activities and seat work; English language -- Composition and exercises -- Study and teaching (Elementary); Literature -- Study and teaching (Elementary); Teaching -- Aids and devices; Creative activities; English language -- Composition and exercises -- Study and teaching; Literature -- Study and teaching; Teaching -- Aids and devices